Biosynthesis And Characterization Of Poly(3-Hydroxybutyrate-Co-3- Hydroxyvalerate) From Cupriavidus Malaysiensis Usmaa1020 Using Glycerin Pitch As Main Carbon Source - Rozina, Rozina (2022)
Plastics are used in almost every part of modern life, from making aeroplanes, cars, and buildings to making clothes, shoes, packaging for food and drinks, and medical devices. As a result, plastic waste is gathered globally, worsening the effects on the ecosystem. Synthetic plastics/conventional plastics takes many years to disintegrate in nature, and incineration produces toxic substances and raises CO2 levels in the atmosphere, causing issues like global warming. As a result, alternatives to petrol-based polymers are being sought. Polyhydroxyalkanoates (PHAs) have been proposed as a feasible substitute for petrochemical-based polymers because of their biodegradable nature. In the present study, Cupriavidus malaysiensis USMAA1020, a Gram-negative bacterium was able to produce biodegradable polymer P(3HB-co- 3HV) by utilizing glycerin pitch which is a by-product of the biodiesel synthesis obtained during the transesterification as low-cost feedstock. The aim of the research was to screen various concentrations of glycerin pitch (5 g/L, 10 g/L, 15 g/L, 20 g/L, 25 g/L), 1-pentanol (0.03 wt% C, 0.06 wt% C, 0.09 wt% C, 0.12 wt% C), ammonium sulfate (0.8 g/L, 1.1 g/L, 1.4 g/L, 1.7 g/L, 2.0 g/L), and different precursors nonaoic acid, valeric acid, propionic acid, with respect to 1-pentanol at concentration of 0.06 wt%C. To enhance the production of PHA, oleic acid concentrations was used as a secondary carbon source.